A157 REAL-WORLD TIGHT OBJECTIVE MONITORING WITH ADALIMUMAB LEADS TO EARLIER DOSE OPTIMIZATION AND HIGHER CLINICAL REMISSION RATES AT 12 MONTHS. (4th March 2021) - Xiao, Y; Al Khoury, A; Golovics, P; Kohen, R; Afif, W; Wild, G; Friedman, G; Galiatsatos, P; Hilzenrat, N; Szilagyi, A; Wyse, J; Cohen, A; et al.
Abstract: Background: Data suggests that tight objective monitoring of inflammatory bowel diseases (IBD) may improve one-year clinical outcomes. Aims: The goal of this study is to assess the adherence to serial tight objective monitoring, via clinical symptoms and biomarkers, and the effect of such tight monitoring on one year outcome in IBD patients at an academic and an university-affiliated center. Methods: We retrospectively reviewed the chart of 428 consecutive IBD patients who started adalimumaby at the McGill University Health Center and Jewish General Hospital (Montreal, Canada) between January 1, 2015 and January 1, 2019 [338 Crohn's disease(CD), 90 ulcerative colitis(UC)]. Clinical symptoms (assessed by Harvey-Bradshaw-Index and partial Mayo), C-Reactive Protein(CRP), and fecal calprotectin(FCAL) were captured at treatment initiation and at 3, 6, 9, and 12 months. Combined adherence was defined as the evaluation of ≥2 of 3 parameters(clinical, CRP, FCAL). Dose optimization and drug sustainability curves were plotted by Kaplan-Meier method. Results: Clinical symptoms were assessed in nearly all patients at 3 (CD-UC:95-94%), 6 (90-83%), 9 (86-85%) and 12 (96-89%) months. CRP was also available for most patients but the frequency of assessment decreased in CD patients over the study period. In comparison, compliance to serial FCAL testing was low throughout the follow-up period. Clinical remission at one-year was significantly higher in patients who were adherent to early assessment visit at 3 months (p=0.001 both for CD and UC). Adherence to early follow-up also resulted in earlier dose optimisation in both CD and UC patients(pLogrank=0.026 for UC and p=0.09 for CD). However, the overall drug sustainability did not differ. Conclusions: Clinical assessment and CRP, but not FCAL, were frequently assessed in patients starting adalimumab. Adherence to early objective combined follow-up visits resulted in earlier dose optimization and improved one-year clinical outcomes but did not change drug sustainability rates. Funding Agencies: None